Influence of Fluid on Seal and Assembly of Pipeline Fittings Based on the Multiscale Finite Element Model - Yangyang Yan; Yaping Fan (Complexity)
Pipeline fittings with ferrules are applied to connect sections of hydraulic pipelines in aircraft, and their reliability and stability are essential. This paper aims at investigating the influence of internal fluid on the sealing characteristics of pipeline fittings by employing the multiscale model. Changes in the sealing characteristics induced by the fluid pressure switch are studied, and the assembly method under the internal fluid is also explored. The calculated results show that the multiscale model can accurately reflect the changes in the sealing area, and the high-pressure fluid can enhance the sealing reliability. Compared with the contact area, the fluid pressure exerts a greater influence on the change in the area of the high-stress zone. Furthermore, the unrestored sealing area enlarges with the increased maximum fluid pressure, and the change in the area of the high-stress zone is significantly larger than that in the contact area. Moreover, the optimum assembly position of ferrule decreases with the increase in fluid pressure, thus achieving the excellent sealing characteristics.